(3GdJShjb GdUMj hGdELJeGYjs - (3YKeGf QOjfI(B, (3jhSas ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2008)
(3fTCI hJWhQ GdNOeGJ GdUMjI, GdJNWjW GdGSJQGJjLj dJUfjY hJWhjQ GdefJLGJ GdUMjI, eaghe GdJShjb GdUMj hGdefJLGJ GdUMjI, JhRjY hJQhjL GdNOeGJ GdUMjI, GdJSYjQ GdYfGUQ GdGVGajI ddeRjL GdJShjbj ddNOeGJ, GdJShjb GdGLJeGYj, Gge GdfXQjGJ hGdfeGPL aj GdJShjb GdGLJeGYj, fehPL hYedjI GdJShjb, GSJQGJjLjGJ GdJShjb GdGSJQGJjLjs
(3HHdjhZQGajG(B: (3U(B.281s
Keywords: (3GOGQI GdeHjYGJs; (3GdJShjbs; (3GdNOeGJ GdUMjIs; (3GdNOeI GdGLJeGYjIs; (3GdQYGjI GdUMjIs